Roman kitchenware discovered in the military environment in Dobrudja - Honcu, Ștefan (Rei Cretariae Romanae Fautorum Acta, 2022)
The aim of the present paper is to present the kitchenware category which comes from the military camps of Dobrudja (Durostorum, Troesmis and Noviodunum). The study includes published and unpublished ceramics produced locally in each site and imported, the last one in low proportion. The kitchenware includes pots, casseroles, frying pans, strainer, bowls, buckets and lids. The pots were divided into 13 types, one of which is imported from the Aegean area and one belonging to the local population (traditional La Tène pots). The casseroles were divided into three types, imported from the Aegean area. There are five types of pans. Among them, one type comes from the Western part of the Empire, and it belongs to the Pompeian red slip ware. The bowls were divided into nine types, most likely produced within each site. Other categories of kitchenware that have been discovered in smaller quantities are: mortaria (two types), buckets (one type) and strainers (one type). The kitchenware from the military camps of Dobrudja dates back to the period between the 1st and 3rd centuries AD.